Estimating genetic gains for tolerance to stress combinations in tropical maize hybrids - Menkir, Abebe; Dieng, Ibnou; Meseka, Silvestro; Bossey, Bunmi; Mengesha, Wende; Muhyideen, Oyekunle; Riberio, Priscillia F.; Coulibaly, Mmadou; Yacoubou, Abdoul-Madjidou; Bankole, Folusho A.; Adu, Gloria Boakyewaa; Ojo, Tayo (Frontiers in Genetics, 2022)
Maize is a strategic food crop in sub-Saharan Africa. However, most maize growing tropical savannas particularly in West and Central African experience the occurrence of frequent droughts and Striga infestation, resulting in significant yield losses. This production zones need maize cultivars that combine tolerance to the two stresses. IITA in collaboration with national partners has thus employed a sequential selection scheme to incorporate both drought tolerance and Striga resistance in topical maize hybrids using reliable screening protocols. The main objective of the present study was therefore to use the data recorded in regional collaborative hybrid trials conducted for eight years under manged stressful and non-stressful conditions and across rainfed field environments for estimating genetic gains in grain yields achieved using this breeding approach. Annual estimates in yield gains were 11.89 kg ha-1 under MDS and 86.60 kg ha-1 under STRIN with concomitant yield increases of 62.65 kg ha-1 under WW conditions, 102.44 kg ha-1 under STRNO and 53.11 kg ha-1 across rainfed field environments. The realization of yield gain under stressful conditions were associated with improvements in plant growth and the resultant potential increase in supply of photosynthate to the developing ears. Further examination of the genetic correlations showed that improvements in grain yield under both MDS and STRIN were achieved without compromising improvements in grain yield across diverse rainfed conditions. The sequential selection scheme can therefore be used to generate hybrids with dependable yields to reduce chronic food deficits in rural communities that experience simultaneous presence of drought and S. hermonthica infestation in production fields.